HIGH-CALORIE DIET DURING LACTATION PROGRAMS EARLY HYPERPHAGIA IN MALE AND FEMALE NEWBORN RATS (Arquivos do Mudi, 2023)
Obesity is a serious and concerning disease for public health. Breastfeeding is crucial formetabolic programming and plays an important role in controlling newborn metabolism. Theaim of this study was to analyze weight gain and milk consumption in male and femalenewborn rats whose mothers were fed a high-calorie diet during the breastfeeding period. Atdelivery, female Wistar rats were divided into two groups, one was fed a hypercaloric diet(4,500 kcal/g and sucrose solution at 10%; Ob group), while control dams were fedcommertial diet (Cont group). Pups were weighed every two days, and milk intake wasrecorded on the 6 th , 11 th and 16 th days old. At 22 days old, the pups were weaned, and themother rats were euthanized for analysis. At 6 th day olds, Ob males consumed 42.7% moremilk than Cont, while Ob females consumed 33.9% more than Cont (P<0.001). On the 11 thday of life, Ob males consumed 42.7% more than Cont, while Ob females consumed 33.9%more than Cont (P<0.05). On the 16 th day, Ob males consumed 39.3% more than Cont(P<0.001), while Ob females consumed 29.8% more than Cont (P<0.01). During thebreastfeeding period, there was an increase in body mass of Ob males by 21.7% (P<0.05) andin females by 10%. It was observed that Ob males showed a weight increase of 18.65%compared to Ob females (P<0.001), while among the Cont group pups, no significantdifference was observed between males and females. We concluded that offspring breastfedby mothers who consumed a high-calorie diet during lactation are more likely to developearly hyperphagia, and a greater risk of developing obesity.